LITERASI SAINS REMAJA BERBASIS HOTS (High Order Thinking Skills) DALAM PEMBELAJARAN BUDIDAYA TANAMAN KOPI - Jaenal Mutakim; Ahmad Tijari Tijari (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2022)
Life in the 21st century demands literacy skills. The ability to understand a concept and understand the process is very useful in order to solve problems faced in the daily life of learning residents. Science literacy is useful if in the process it is equipped with a high level of thinking skills in order to develop the potential possessed to find solutions or new ideas in conditions of always living situations. This study aims to see the science literacy ability of hots-based adolescents (Higher Order Thinking Skill) in learning activities for coffee plant cultivation in remote communities in West Java. Learning is carried out outside the classroom with an Education training plus approach. The ability to think of adolescents indicates the ability of scientific literacy in identifying, making decisions, and concluding related to the cultivation of coffee plants in their village environment. The results showed that the science literacy ability of HOTS-based adolescents is still at a low level, adolescents are at the conceptual knowledge level, while their thinking ability is still in analytical skills. The thinking ability of adolescents is closely related to aspects of scientific literacy that are understood to be related to the concept of coffee plant cultivation that is commonly found in the daily life of teenagers around coffee plantations. Research findings in the field found that learning residents have not actively sought sources of information for ideas in broad media, learning resources and activities. Youth should develop a positive attitude towards science learning in order to improve science literacy and build a high level of thinking skills. The ability to think analytically, assess and create adolescents can be improved by diligently reading, doing Journaling, asking a lot of questions or with useful games.